THE TOXICOLOGICAL GEOCHEMISTRY OF EARTH MATERIALS: AN OVERVIEW OF PROCESSES AND THE INTERDISCIPLINARY METHODS USED TO UNDERSTAND THEM - Plumlee G.S.; Morman S.A.; Ziegler T.L. (My University, 2006)
In this chapter, we have provided a comparatively brief overview of the myriad potential geochemical and biochemical processes that can occur when earth materials come into contact with body fluids via inhalation, ingestion, or percutaneous exposure routes. We have also shown how a wide variety of earth science methods have been and can be integrated with health science methods to better understand the potential health effects that might be associated with exposure to diverse earth materials. As noted by Plumlee and Ziegler (2003, 2006), it is possible to group individual earth material components according to how they behave in vivo, as well as by similarities in how they trigger toxicity: • Bioreactive earth materials can substantially modify the chemical composition of body fluids and tissues, to produce tissue irritation or more serious alkali or acid burns. • Solubilization of bioaccessible toxicants from earth materials and their subsequent absorption can produce toxic effects in the body. • Exposure to earth materials that are insoluble (biodurable) in body fluids can trigger toxic responses as the body attempts to clear the materials. • Pathogens associated with earth materials can trigger disease. • The body's immune response to the earth materials or toxicants contained within the earth materials can trigger a toxic response. All of these different these types of health effects are strongly influenced by the forms in which earth materials are delivered to the body (mineralogy; particle size and morphology; particle solubility, alkalinity, acidity; oxidation state of contained constituents; and others). These health effects all also ultimately require some level of chemical interactions between the earth materials and body fluids. However, most earth materials are complex mixtures of many different components, each having a particular mix of bioreactivity, biosolubility, and biodurability characteristics. Potentially complex chemical interactions between the various earth material components and the body's fluids may result. Hence, as the potential health effects of complex earth materials are assessed, it should always be kept in mind that the integrated physical and chemical characteristics, chemical behavior in vivo, and resulting toxicity effects of the whole material may be substantially different from those of its individual components.. These conclusions implicitly require important roles for the earth scientist in helping to both characterize earth materials and understand geochemical processes in the context of the physiological processes of the human body. Many studies have been carried out to address this complex but fascinating topic; however, as indicated by the sections on asbestos and lead, there are many unresolved questions remaining. There should therefore be ample opportunities for fruitful future collaborations to occur between geochemists, toxicologists, physiologists, epidemiologists, and other biomedical disciplines. Copyright © Mineralogical Society of America.